Understanding diverse subjectivities of medical students in seeking composite role models: A Q-methodology study - Reihaneh Hasani; Elaheh Mohammadi; Ali Norouzi; Mahboobeh Khabaz Mafinejad (PLoS ONE, 2026)
Background Role modeling, an integral part of medical education, is a complex and multifaceted process. To unravel the hidden dimensions of role model selection, a comprehensive understanding of students’ subjectivities is crucial. This research aimed to elucidate the dominant subjectivities of medical students when selecting composite role models. Methods This study employed the Q-methodology to investigate individuals’ subjectivities and portray them. Initially, we formulated Q-statements based on semi-structured interviews with students and a literature review. In the second step, 31 undergraduate medical students were selected through purposive and snowball sampling. In the next step, data were collected using a questionnaire and a Q-grid. In the fourth step, we categorized individuals using KADE software and performed factor analysis. Finally, the research team utilized factor arrays and combined quantitative and qualitative data to interpret the dominant subjectivities in the selection of composite role models. Results This study identifies four dominant subjectivities among 31 undergraduate medical students, explaining 50% of total variance, including: 1) Relying on professional and skillful role models (n = 13, 34% variance): students emphasize professional behavior, responsibility, and strong teaching competence, 2) Relying on popular and famous role models (n = 4, 6% variance): students value fame at micro to macro levels, including clinical excellence and international engagement, 3) Relying on venerable and value-oriented role models (n = 6, 6% variance): students prioritize moral principles, ethical conduct, and alignment with personal values, 4) Relying on social and responsive role models (n = 5, 4% variance): students highlight social engagement, altruism, and a positive impact on society. Discussion Our research indicates that multiple factors significantly influence students’ selection of composite role models, with varying subjectivities across four domains. Teachers can use these subjectivities to reflect on the factors involved in role modeling. Medical schools can leverage these identified subjectivities to enhance role modeling and improve teaching and learning.